Internal Audit Capability Level: Preliminary Study of Federal and State Statutory Body in Malaysian Public Sector Organizations - Nur Ain Zakiah, Mohd Yusof; Hasnah, Haron; Ishak, Ismail (Universiti Malaysia Pahang, 2017)
The purpose of this paper is to explain the importance of internal audit in enhancing the good governance of Malaysian public sector organizations. The primary objective is to determine the capability level of internal audit units of the different entities of organizations i.e. federal statutory body (CSA) and state statutory body (CSB). An explanatory case study method was used to collect the data whereby semi structured interviews, informal conversations, questionnaire and document reviews were conducted. It is found that CSA achieves overall capability level 2 with 76% achievement of key process areas (KPAs) while CSB only scores overall capability level 1 with 52% overall percentage achievement of KPAs. However, CSB scores higher percentage for respective elements of services and role of internal auditing, people management and performance management and accountability compared to CSA. Instead, CSA scores 100% achievements of KPAs for other three dimensions i.e. professional practices, organizational relationships and culture and governance structure. There is a critical need to review the dimensions of services and role of internal audit and people management, for both organizations in order to enhance the effectiveness of the IA function. Implications and suggestions for further studies are also provided.